The Right to Survival in the Democratic People’s Republic of Korea - SONG, Jiyoung (Institutional Knowledge at Singapore Management University, 2010)
For the past decade, the author has examined North Korean primary public documents and concludes that there have been changes of identities and ideas in the public discourse of human rights in the DPRK: from strong post-colonialism to Marxism-Leninism, from there to the creation of Juche as the state ideology and finally 'our style' socialism. This paper explains the background to KIM Jong Il's 'our style' human rights in North Korea: his broader framework, 'our style' socialism, with its two supporting ideational mechanisms, named 'virtuous politics' and 'military-first politics'. It analyses how some of these characteristics have disappeared while others have been reinforced over time. Marxism has significantly withered away since the end of the Cold War, and communism was finally deleted from the latest 2009 amended Socialist Constitution, whereas the concept of sovereignty has been strengthened and the language of duties has been actively employed by the authority almost as a relapse to the feudal Confucian tradition. The paper also includes some first-hand accounts from North Korean defectors interviewed in South Korea in October–December 2008. They show the perception of ordinary North Koreans on the ideas of human rights.